Effects of HMB supplementation on hormonal adaptations following resistance training: a systematic review and meta-analysis - Shakibaee, A.; Gholizadeh, M.; Shirvani, H.; Samadi, M. (Sport Sciences for Health, 2023)
Purpose The aim was to perform a meta-analysis of studies examining the effects of ß-hydroxy-ß-methylbutyrate (HMB) supplementation on hormonal adaptations after resistance training.